( N ,Δ λ ) - Salwa Salwa; Qurratul Aini; Ni Wayan Switrayni (Publisher : Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Sequence spaces is one of interesting topic of analysis research. Some of that are convergent and bounded sequence. In this paper we define some releated BK spaces (N̅,Δλ) ∞, (N̅,Δλ), dan (N̅,Δλ)O some characteristics releated to them. Moreover we determine their β-dual.